Quadratus lumborum blocks for abdominal transplant surgeries at UPMC Children's Hospital of Pittsburgh—A five year experience. (22nd April 2022) - Hernandez, Maria A.; Licata, Scott; Damian, Daniela; Ganoza, Armando; Visoiu, Mihaela
Abstract: Background: Adequate perioperative analgesia for pediatric abdominal transplant surgery is essential for patient recovery. However, the risks of commonly used medications such as hepatotoxicity, nephrotoxicity, bleeding concerns, and poor graft results with opioids limit pain management in this population. Thoracic epidural, continuous erector spinae plane, and type‐1 quadratus lumborum blocks (QLBs) have been described and utilized in the adult population in this setting. The safety and benefits of regional anesthetic techniques in pediatrics have been widely documented for different types of procedures except pediatric abdominal transplantation, where data remains scarce. Our primary goal was to determine if QLBs provided adequate perioperative analgesia when part of a multimodal approach. Secondary objectives were to examine complications and effects on the intensive care unit (ICU) and hospital stay. Methods: We performed a retrospective, observational study of pediatric patients who underwent abdominal transplant surgeries at the University of Pittsburgh Medical Center Children's Hospital of Pittsburgh from January 2015 to July 2021 and received a single injection QLB for pain control. Data collected included: demographics, nerve block characteristics, perioperative opioid consumption, use of non‐opioid analgesia, daily pain scores, and hospital and ICU stay. Results: Forty‐two patients met the inclusion criteria for our study. Our results suggest that QLBs decrease opioid consumption, facilitate early extubation, prevent reintubation in the ICU, and reduce ICU and hospital stay. Conclusions: QLB is feasible and can be used as a multimodal approach for postoperative pain control in pediatric solid organ transplantation.